SISTEM INFORMASI AKADEMIK SEKOLAH PADA SMK TADIKA PERTIWI BERBASIS WEBSITE - Nur Muhamad Rizki, - (2018)
SMK Tadika Pertiwi is one of the Private Vocational Schools located in Depok City. School is one of the organizational means in providing services to the public in the field of education. One of the most important parts of a school is the student and the student's grade. In one school there are hundreds of students and each has different values. Not infrequently the storage of student value, attendance list of students, up to the payment of SPP recorded and stored conventional. So it takes a very long time in the process. This also causes the parents can not at any time check data son / daughter in school. The purpose of utilizing Web-based computerized information systems, MySQL, XAMPP in order to manage school administration can simplify the data storage in every student-siswainya. The results of research conducted is in the form of the value of report cards delivered on the process of taking report cards every semester